Searching for Islamic ethical agency in post-apartheid Cape Town : an anthology - Fataar, Aslam (Beyers Naudé Centre series on public theology ;)
"The compositions brought together in this book began a quarter of a century ago in 1994, with the onset of South Africa⁰́₉s non-racial democracy, and in one way it may be viewed as the critical observations of an organic intellectual⁰́₉ engaging the exigencies of life during the first 25 years of South Africa⁰́₉s democracy."--Publisher's description.